2011 IEEE Workshop on Applications of Signal Processing to Audio and Acoustics (WASPAA) 2011
DOI: 10.1109/aspaa.2011.6082331
|View full text |Cite
|
Sign up to set email alerts
|

Spectral vs. spectro-temporal features for acoustic event detection

Abstract: Automatic detection of different types of acoustic events is an interesting problem in soundtrack processing. Typical approaches to the problem use short-term spectral features to describe the audio signal, with additional modeling on top to take temporal context into account. We propose an approach to detecting and modeling acoustic events that directly describes temporal context, using convolutive non-negative matrix factorization (NMF). NMF is useful for finding parts-based decompositions of data; here it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 5 publications
0
71
0
2
Order By: Relevance
“…In addition, F and G were implemented using fully-connected DNNs, and the symmetric network architecture of F was used for that of G. Then, F and G were trained to maximize (12) and to minimize (19) and (20), alternately.…”
Section: B Acoustic Feature-extractor Optimization Using Variationalmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, F and G were implemented using fully-connected DNNs, and the symmetric network architecture of F was used for that of G. Then, F and G were trained to maximize (12) and to minimize (19) and (20), alternately.…”
Section: B Acoustic Feature-extractor Optimization Using Variationalmentioning
confidence: 99%
“…To extract a set of acoustic features for the soundidentification problem, feature-extractor-optimization methods have been actively investigated [12], [13], [14]. These studies have revealed that it is necessary to determine both spectral and temporal characteristics to accurately identify various sounds.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the method of matching pursuit that sparsely decomposes the signal by using over-complete dictionaries has been successfully applied to classify the environmental sounds [2,5]. As in the matching pursuit, the non-negative matrix factorization (NMF) also works on sparse factorization of signals with learning the dictionary; Cotton and Ellis [8] employ the NMF to construct acoustic event-based patch features from a spectrogram. Ye et al [3] utilize the acoustic subspace extracted from sound clips in the kernel-based framework.…”
Section: Introductionmentioning
confidence: 99%
“…NMF-related methods can be separated in those that exploit the NMF activations directly to perform event detection [8,11], and in those that employ a classifier trained on these activations [12,13]. Based on the fact that NMF-based approaches can benefit from the creation of a Mixture of Local Dictionaries (MLD) [14], in [15] the authors propose a classifier-based NMF system using MLDs for improved detection performance.…”
Section: Introductionmentioning
confidence: 99%